2009
DOI: 10.1111/j.1743-6109.2008.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Visual Attention to Sexually Explicit Videos: A Preliminary Study

Abstract: Introduction Although men appear to be more interested in sexual stimuli than women, this difference is not completely understood. Eye-tracking technology has been used to investigate visual attention to still sexual images; however, it has not been applied to moving sexual images. Aim To investigate whether sex difference exists in visual attention to sexual videos. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 25 publications
3
35
1
Order By: Relevance
“…Furthermore, there has been no study to investigate this relation in men with an eye-tracking system as a reliable methodology for assessing visual attention to sexual stimuli, with which we and other researchers have reported a sex difference in sexual interest. 2,6,7 We found clearly by using Pearson's correlation coefficient in this study that, as the degree of paranoia, psychasthenia and social introversion in Sexual interest and personality characteristics in men A Tsujimura et al the personality grew stronger, sexual interest in the sexual region became weaker. Paranoia is a psychology characterized by excessive anxiety or fear.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Furthermore, there has been no study to investigate this relation in men with an eye-tracking system as a reliable methodology for assessing visual attention to sexual stimuli, with which we and other researchers have reported a sex difference in sexual interest. 2,6,7 We found clearly by using Pearson's correlation coefficient in this study that, as the degree of paranoia, psychasthenia and social introversion in Sexual interest and personality characteristics in men A Tsujimura et al the personality grew stronger, sexual interest in the sexual region became weaker. Paranoia is a psychology characterized by excessive anxiety or fear.…”
Section: Discussionmentioning
confidence: 50%
“…2 In brief, eye movements of subjects were measured with a Quick Glance 2 Eye Tracker System (EyeTech Digital Systems, Mesa, AZ, USA; Figure 1). The system consists of EyeTech TM2 software installed on a laptop computer, two infrared lights mounted on each side of the monitor and a camera placed on the keyboard.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method is ideal because sexual interest can be evaluated quantitatively and noninvasively. After using this system, we reported that a sex difference existed in visual attention to a sexual video: men viewed the opposite sex for longer periods than women, and women viewed the same sex for longer periods than men 12) . Interestingly, women paid more attention to the non-human regions than did men.…”
Section: Analysis Of Sexual Interestmentioning
confidence: 99%